2021
DOI: 10.5334/gh.934
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Acute Coronary Syndrome and its Potential Impact on Cognitive Function

Abstract: According to the World Health Organization (WHO) forecasts, in 2030, the number of people suffering from dementia will reach 82 million people worldwide, representing a huge burden on health and social care systems. Epidemiological data indicates a relationship between coronary heart disease (CHD) and the occurrence of cognitive impairment (CI) and dementia. It is known that both diseases have common risk factors. However, the impact of myocardial infarction (MI) on cognitive function remains controversial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…As indicated in Table 1, patients with CI found during hospitalization for MI had significantly lower GFRs (85 (73-101) vs. 90 (76-105); p = 0.02), as well as higher BNP levels (127.4 (73.1-265.1) vs. 96.9 (53.2-199.8); p = 0.01) and lower ejection fraction (48 (41-50) vs. 48 (45-54); p = 0.05), compared to those without deficits. It was also observed that those with CI were significantly older (60.4 (±10.2) vs. 58.3 (±9.3); p = 0.03) and scored higher on the SYNTAX scale (10 (7-16) vs. 9 (6)(7)(8)(9)(10)(11)(12)(13)(14); p = 0.05).…”
Section: Cognitive Impairmentmentioning
confidence: 85%
See 1 more Smart Citation
“…As indicated in Table 1, patients with CI found during hospitalization for MI had significantly lower GFRs (85 (73-101) vs. 90 (76-105); p = 0.02), as well as higher BNP levels (127.4 (73.1-265.1) vs. 96.9 (53.2-199.8); p = 0.01) and lower ejection fraction (48 (41-50) vs. 48 (45-54); p = 0.05), compared to those without deficits. It was also observed that those with CI were significantly older (60.4 (±10.2) vs. 58.3 (±9.3); p = 0.03) and scored higher on the SYNTAX scale (10 (7-16) vs. 9 (6)(7)(8)(9)(10)(11)(12)(13)(14); p = 0.05).…”
Section: Cognitive Impairmentmentioning
confidence: 85%
“…To date, a limited number of studies attempting an assessment of cognitive function in patients after MI have been published. Moreover, their assessment is also not part of routine daily clinical practice among cardiologists [7]. This may be due to the low awareness of the widespread presence of MCI and dementia in their patient population and a focus mainly on cardiovascular problems, neglecting a holistic approach to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Tests for these domains should be included in any reduced assessment, as these domains are typically linked to vascular cognitive impairment and can impede patient insight and motivation and limit the capacity for self-care behaviors. 9 Adding to these difficulties, <30% completed ≥1 session of CR, the most effective intervention to support secondary prevention in ACS. 10 Direct, systematic referral to CR for patients screening positive for MCI as inpatients is recommended to promote prevention 11 and the study results strengthen the recommendation for CR in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, this study showed that multiple cognitive domains may be impaired post-ACS, including executive functioning and processing speed. Tests for these domains should be included in any reduced assessment, as these domains are typically linked to vascular cognitive impairment and can impede patient insight and motivation and limit the capacity for self-care behaviors 9. Adding to these difficulties, <30% completed ≥1 session of CR, the most effective intervention to support secondary prevention in ACS 10.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is the main cause of mortality and morbidity worldwide, causing over 8 million deaths worldwide each year and a huge burden on social care systems [ 1 ]. Asians exhibited greater susceptibility to CAD and diabetes mellitus (DM) compared to Westerners, due to higher levels of central obesity and total adiposity or higher degree of insulin resistance and endothelial dysfunction [ 2 – 4 ].…”
Section: Introductionmentioning
confidence: 99%